International Labor Economics - Hamermesh, Daniel S. (Journal of Labor Economics, 2002)
I argue for increased reliance on non–U.S. data and policy evaluations to understand basic labor market parameters and to predict the effects of changes in U.S. labor market policies. Foreign experiences generate exogenous shocks to labor costs that create unusual opportunities to measure impacts on labor demand. Foreign policies often provide more variation in the underlying parameters in systems that are often structured like their American counterparts. Foreign data sets are often larger and better suited to inferring behavior. An empirical examination shows the effect of author's location, data set, and journal on the research's subsequent impact.